Human anti‐α‐fucose antibodies are xenoreactive toward GGTA1/CMAH knockout pigs. (22nd July 2020) - Burlak, Christopher; Taylor, R. Travis; Wang, Zheng Yu; Tector, A. Joseph
Abstract: Progress has been made in overcoming antibody‐mediated rejection of porcine xenografts by deleting pig genes that produce unique carbohydrate epitopes. Pigs deficient in galactose α‐1, 3 galactose (gene modified: GGTA1 ) and neu5Gc (gene modified: CMAH ) have reduced levels of human antibody binding. Previously we identified α‐fucose as a glycan that was expressed in high levels on cells of GGTA1/CMAH KO pigs. To validate the α‐fucose phenotype observed previously we compared lectin affinity toward human and pig serum glycoproteins by dot blot analysis and confocal microscopy. Human anti‐fucose antibody isolated by affinity chromatography was tested for specificity to L‐fucose by custom macroarray. The affinity and cytotoxicity of the isolated human anti‐fucose antibody toward human and GGTA1/CMAH KO pig PBMCs was determined by flow cytometry. Dot blot and confocal analysis support out previous findings that α‐fucose is more highly expressed in pigs than humans. Pig kidney glomeruli and tubules contain abundant α‐fucose and may represent focal sites for anti‐α‐fucose antibody binding. The Isolated human anti‐fucose IgA, IgG and IgM bound to GGTA1/CMAH KO pig PBMC and were cytotoxic. Interestingly, the isolated human IgG cross reacted with the methyl pentose, L‐rhamnose. Human anti‐fucose antibody bound and was cytotoxic to GGTA1/CMAH KO pig peripheral blood monocytes. We have shown that α‐fucose is an abundant target for cytotoxic human antibody in the organs of genetically modified pigs important to xenotransplantation.